VISUALISASI KONSEP-KONSEP BIOLOGI DENGAN MENGGUNAKAN DIAGRAM ROUNDHOUSE - Yuni Wibowo (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Biology as one area of science provides a variety of learning experiences to understand the concept and process of science. According to the School Based Curriculum (SBC), one of the goals of biology as a secondary level subject is to develop mastery of concepts and principles of biology and it’s association with other science and to develop the students’ knowledge, skills and self-confidence. The scope of biology as a subject includes the true meaning of biology, diversity, classification, ecosystems, cellular organization, structure and function, growth and development, hereditary, evolution, and biotechnology.The scope of biology materials that exist in the SBC shown that there are materials that can be developed with process skills but there are also materials that focuses on the acquisition of biological concepts. Furthermore, so far the study of biological concepts tend to be learned in bits and pieces that made it so easily forgotten by students. Therefore, efforts is needed to bring the information obtained by students to be stored long-term memory so that the students will remember it longer. Roundhouse diagram is one of learning techniques to strengthen memory by storing the information obtained into the students' long-term memory. Roundhouse diagram learning techniques is an application of meaningful learning which arrange sub-concept in a structure of knowledge in the form of a circle completed by visual symbols and key words.